Anger and fear: effects of negative emotions on hotel employees' information technology adoption. Issue 5 (5th February 2021) - Zheng, Lili; Montargot, Nathalie
Abstract : Purpose: The use of information technology (IT) in the hospitality industry is driven by the need to improve and refine customer service. However, it is unlikely that new IT will be successfully implemented if employees' roles and emotions are overlooked. The purpose of this study is to examine the interplay of negative emotions (anger and fear), coping strategies (venting anger and psychological distancing), perceptions of an IT innovation and intention toward adopting it. Design/methodology/approach: A research model is developed based on the cognitive appraisal theory of emotion, coping theory and innovation diffusion theory. An online survey was conducted among employees working for hotels that had deployed a new reservation system, and 234 responses were collected. Findings: The results indicate that employees' negative emotions (anger and fear) have negative and significant effects on their perceptions of adopting a new reservation system through coping strategies (i.e. venting anger and psychological distancing). Furthermore, employees' perceptions of adopting an innovative reservation system have a positive effect on their adoption intention toward the system. Originality/value: To the best of our knowledge, this is the first research to address the impact of distinct emotions on IT innovation adoption, as well as explaining the relation between affective and cognitive effects. The findings demonstrate the importance of examining negative emotions in IT innovation adoption. In addition, the model developed in this study confirms that an appraisal tendency approach better specifies the conditions under which different emotions are triggered to predict and explain how emotions relate to IT use through adaptation behaviors when compared with a valence-based approach.